Can the Alexander Technique improve balance and mobility in older adults with visual impairments? A randomized controlled trial. (March 2015) - Gleeson, Michael; Sherrington, Catherine; Lo, Serigne; Keay, Lisa
Objective: To investigate the impact of Alexander Technique lessons on balance and mobility in older adults with visual impairments. Design: Randomized assessor blinded controlled trial with intervention and usual care control groups. Setting: Participants' homes. Subjects: A total of 120 community-dwellers aged 50+ with visual impairments. Intervention: Twelve weeks of Alexander lessons and usual care. Main outcome measures: Short Physical Performance Battery items were primary outcomes at 3 months and secondary outcomes at 12 months. Additional secondary outcomes were postural sway, maximal balance range and falls over 12 months. Results: Between-group differences in primary outcomes were not significant. The intervention group reduced postural sway on a firm surface with eyes open at 3 months after adjusting for baseline values (–29.59 mm, 95%CI −49.52 to −9.67, P < 0.01). Planned sub-group analyses indicated a greater intervention effect among past multiple-fallers (2+) than non-multiple fallers for gait speed ( P = 0.02) and step length ( P < 0.01) at 3 months and chair stand at 12 months ( P < 0.01). There was a non-significant reduction in falls rate (IRR = 0.64, 95%CI 0.34 to 1.15, P = 0.13) and injurious falls (IRR = 0.61, 95% CI 0.28 to 1.30, P = 0.20) in the intervention group compared to the control group. Conclusion: The intervention did not have a significant impact on the primary outcomes but benefits for the intervention group in postural sway, trends towards fewer falls and injurious falls and improved mobility among past multiple-fallers suggest further investigation of the Alexander Technique is warranted.